The Influence of Trustworthiness and Parasocial Interaction on Purchase Intention of Bening’s Clinic Lampung Products - Clara, Kerin Yolanda; Roslina (MULTIPLE: Journal of Global and Multidisciplinary, 2024)
In contemporary marketing, social media influencers significantly impact by endorsing products to their followers. For an influencer to effectively generate purchase interest, they must be deemed credible. This research examines how trustworthiness and parasocial interactions influence the purchase intentions of followers towards Bening's Clinic Lampung products, particularly those following influencer Andhita Irianto. The study utilizes primary data collected through questionnaires from 136 respondents, selected via Purposive Sampling within a Nonprobability Sampling framework, along with secondary data. The analysis methods include validity and reliability tests, multiple linear regression, and hypothesis testing through t-tests, F-tests, and the coefficient of determination (R2). Findings reveal that both trustworthiness and parasocial interactions with Andhita Irianto positively and significantly impact followers' intentions to purchase Bening's Clinic Lampung products.